Komparasi Self-Control Generasi Z terhadap Adiksi Internet - Fikra, Hidayatul (JURNAL PSIKOLOGI, 2024)
The internet has infiltrated Generation Z's world in almost every aspect of their lives. If generation Z does not have high self-control, addiction to the internet is inevitable. This study aims to analyze self-control in generation Z according to their internet addiction category. This research uses a descriptive-analytical method with a qualitative approach. The level of internet addiction is known with the Internet Addiction Test, then interviews are conducted to explore and describe the picture of self-control in generation Z. The results of the study found that out of nine respondents, there are nine respondents. The results found that out of nine respondents, there were four people with mild addiction category and five others with moderate addiction category. Respondents in the low category have high self-control as shown by time management skills, avoiding negative impulses from the internet, and using the internet as needed. The implication of this study is that Generation Z is easily distracted and responds to internet stimulus, making them vulnerable to internet addiction. Self-control is one of the things that really needs to be developed so that generation Z can avoid internet addiction.